A systematic review on cardiovascular stent and stenting failure: coherent taxonomy, performance measures, motivations, open challenges and recommendations - Kareem, A. K.; M. Gabir, Mustafa; Almoayed, O. M.; Ismail, A. E.; Taib, Ishkrizat; Darlis, Nofrizalidris; Ali, I. R. (Penerbit UTHM, 2022)
Cardiovascular stenting is a mature topic but it is still being developed in the research community because of its importance. To provide worthy information about cardiovascular stenting environments and to give support to the researchers, attention must be given to understand the obtainable choices and gaps in this research field. This work aims to examine and examine the literature of each work related to the placement of cardiovascular stents, the failure of the stents and the models of stent designs to provide a good understanding through the investigation of articles published in various contextual aspects, such as motivations, open-challenges and recommendations to improve the field of stent placement. A systematic review is carried-out to map and examine the articles related to cardiovascular stents, the failure of the stents and the models of stent designs through a coherent-taxonomy used in three well-known scientific databases: ScienceDirect, IEEE Explore, and Web of Science. These databases involve literature that highlight arterial stenting. Based-on our inclusion and exception, a total of 90 articles composed the final set that offer various classes and sub-classes. The first class includes the development studies with (42/90) of experimental, computational and combined experimental and computational studies related to stent models performance and stent failure, the second class discussed studies that have been performed on stent design with (32/90), the third class is focused on the framework studies with (10/90), and the fourth class includes problems of stenting long-term with (6/90). The performance of stent designs, which is a research area that requires periodic controls, tools and procedures that could provide a stent design with good mechanical performance, reduce restenosis in the stent and increase fatigue resistance and durability. There have been numerous studies on stent performance that could promise good results in this field. The fields of research in stent designs vary, but all fields are fundamental equally. The expectation of this work could help to emphasize present research chances and, therefore, expand and make further research fields.